Fates of potassium during co-pyrolysis of corn stalk and plastic film components - Chao Fan; Jing Liu; Junxia Wang; Jian Li; Zixi Han; Xiaoqiang Cui; Zhanjun Cheng; Beibei Yan; Guanyi Chen; Jingang Yao (Biomass and Bioenergy, 2027)

Proteomic responses of Phaeocystis globosa during colony development promoted by Skeletonema costatum culture filtrate - Shufei Zhang; Beibei Han; Anji Lian; Fengxia Wu; Huaxue Liu; Honghui Huang (Marine Environmental Research, 2026)

Efficacy and durability of therapies for neurogenic lower urinary tract dysfunction: A network meta-analysis of Botulinum Toxin a, instillations, and neuromodulation - Beibei Lei; Cunyu Lan; Yage Wang; Shenhong Ma; Heling Wang; Di Zhang; Qiaohua Han; Weisheng Zhuang (Toxicon, 2026)

Microbial–enzymatic associations with a U-shaped sweet aroma trajectory and the progressive development of woody, herbal, and aged notes during long-term aging of Shoumei white tea - Xingyu Long; Beibei Wen; Xiaobo Liu; Hongying Huang; Luqin Zhu; Taolin Chen; Yongchao Liang; Yongquan Xu; Xiaohong Wang; Jiaojiao Qu; Shumei Han; Jianjun Liu; et al. (Food Research International, 2026)

Fermentation optimization and characterization of extracellular protein-associated antifungal components from Bacillus velezensis SY01 against Cytospora pyri - Shuaishuai Sha; Lingkai Xu; Canpeng Fu; Qiuyan Han; Jiaqi Ding; Beibei Feng; Yan Zhang; Sabinur Nurmemet; Pan Xie (Physiological and Molecular Plant Pathology, 2026)

Carbon radical-promoted NH bond breaking for biomass-derived amino acids to nitriles on low-coordinated Ni centers - Huiwen Zhang; Xia Zhang; Yue Ma; Yingnan Zhao; Rui-Qi Yao; Xinying Sun; Tonghui Wang; Beibei Xiao; Gao-Feng Han; Xing-You Lang; Qing Jiang (Chemical Engineering Journal, 2026)

Precise engineering of bimetallic sites via molecular coordination strategy for enhanced bifunctional oxygen electrocatalysis - Zhenbei Yang; Zhe Wang; Han Liu; Xiaoyan Jin; Qitong Ye; Zhe Lu; Ruojie Xu; Beibei Yu; Yifan Zhang; Kexin Kong; Yipu Liu; Seong-Ju Hwang; et al. (Science Bulletin, 2026)

Cordycepin inhibits human extravillous trophoblast invasion by suppressing snail-mediated MMP2 expression - Manman Guo; Siwei Luo; Beibei Bi; Xiaoyu Han; Yuanyuan Jia; Jung-Chien Cheng; Lanlan Fang (Tissue and Cell, 2026)

PpZAT10 inhibits PpTST1 expression to regulate sugar accumulation in peach (Prunus persica) fruit - Qinqi Liu; Beibei Feng; Liuqing Han; Dongsheng Wang; Kexin Liu; Xiaobei Wang; Nan Hou; Lei Wang; Xianbo Zheng; Xiaodong Lian; Jun Cheng; Wei Wang; et al. (Plant Science, 2026)

Quality control and spectrum–effect relationship of Crataegus pinnatifida polysaccharide from different habitats - Yongshuai Jing; Qiyuan Han; Ziyan Li; Yingqi Li; Xiaoyu Chang; Beibei Hu; Lanfang Wu (Natural Product Research, 2026)

Study on the mechanism of fat coal compatibility driven by structure transformation - Xuhui Chen; Ruyuan Duan; Ruifang Hou; Xin Jin; Bo Wu; Yanfeng Shen; Beibei Cui; Liping Chang; Chunhao Liang; Xinjie Han; Meijun Wang (Fuel, 2026)

Functional role of aquaporin 3 in osmoregulation, intestinal homeostasis, and antiviral defense in Pacific white shrimp (Litopenaeus vannamei) - Zhongkai Wang; Beibei Wang; Kunpeng Zhao; Wanyu Han; Peiliang Liu; Xuan Song; Ao Diao; Yunxing Chen; Wenjuan Liu; Yuquan Li (Fish & Shellfish Immunology, 2026)

IL-37 attenuates HEI-OC1 cell senescence by modulating the NF-κB pathway - Luan Xu; Beibei Xu; Liya Ding; Shumin Li; Xiaopei Wu; Guanghui Wang; Yuefeng Han (Molecular & Cellular Toxicology, 2026)

Enhancing maize aboveground biomass estimation through time-series UAV-based multispectral and thermal imagery and improved FAO66 model - Guomin Shao; Wenting Han; Huihui Zhang; Beibei Zhou; Yi Wang; Yu Zhang; Li Yuan Zhang; Yaxiao Niu; Quan Xue (International Journal of Remote Sensing, 2026)

Straw return improves soil multifunctionality by altering functional microbial diversity and abundance - Wenkang Yan; Mingyang Xia; Jiahao Liu; Zhixiang Han; Zhong Li; Christopher Rensing; Hend A. Alwathnani; Beibei Chen; Wenge Wu; Hongmiao Wu (Agriculture, Ecosystems & Environment, 2026)

The PpEIL2/3-PpWRKY45A/B-PpMIF2 transcription cascade regulates ethylene-induced filament senescence in peach - Charmaine Ntini; Sylvia Cherono; Huasheng Huang; Beatrice Nyambura Njuguna; Juanli Sun; Yudi Liu; Wen Xiao; Beibei Zheng; Ruo-Xi Zhang; Yunpeng Cao; Yuepeng Han; Yun Zhao (Postharvest Biology and Technology, 2025)

Assessing a dynamic CO2 input and response module in SWAT for simulating climate-induced phosphorus loss and economic costs - Na Wen; Yue Wang; Beibei Ding; Yiwen Han; Junyu Qi; Srinivasulu Ale; Puyu Feng; De Li Liu; Raghavan Srinivasan; Yong Chen (Journal of Hydrology, 2025)

Chitosan-derived nanoemulsion enriched with Streptomyces metabolites for target control of tobacco leaf spot, enhanced foliar retention and plant nutrition - Xue Han; Chunli Xu; Rui Yang; Dan Chen; Yaning Li; Beibei Ge (Chemical Engineering Journal, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Botulinum Toxin A (BTA) for pain and function improvement in osteoarthritis: a systematic review and meta-analysis of clinical efficacy evidence from randomized controlled trials - Beibei Lei; Weisheng Zhuang; Yage Wang; Shenhong Ma; Heling Wang; Di Zhang; Qiaohua Han; Xu Wang; Qixin Ding; Yuefang Li (Toxicon, 2025)

Synergistic Mn-doping and MXene coupling in sulfur-deficient In2S3 nanosheets for high-performance sodium-ion batteries - Manman Zhang; Qi An; Haocun Ba; Boxi Wang; Beibei Li; Chengjiang Deng; Liuyuan Ma; Yinghong Lan; Xiaoyan Han; Shaozhuan Huang (Chemical Engineering Journal, 2025)

Global sensitivity analysis of SIMDual-Kc for modeling evapotranspiration in maize field under film-mulched and drip irrigation - Hexiang Zheng; Biyu Wang; Xuanxuan Wang; Haofang Yan; Jiabin Wu; Guoqing Wang; Rongxuan Bao; Beibei Hao; Yujing Han (Irrigation Science, 2025)

Bioplastics (PC/GL) versus non-biodegradable plastics (PE/PP): Effects on growth and rhizosphere soil microbial-metabolomics of Houttuynia cordata - Mei Li; Beibei Zhao; Xiao Han; Jie Jiang; Chuanhuan Liu; Yingzhu Liu (Journal of Hazardous Materials, 2025)

Sex-and stage-specific effect of prenatal exposure to organophosphate esters with children's physical growth patterns and adiposity rebound timing: Modification by breastfeeding - Xing Wang; Juan Tong; Han Li; Mengjuan Lu; Yuan Liu; Hong Gan; Yifan Wang; Menglong Geng; Xuejiao Qie; Xiulong Wu; Hui Gao; Beibei Zhu; et al. (Journal of Hazardous Materials, 2025)

Chitin nanowhiskers-stabilized Pickering emulsions for encapsulating flavor compounds in Zanthoxylum bungeanum oil - Xiaoxue Yin; Fangjiao Chen; Bingyu Han; Xuedong Wang; Wenping Ding; Beibei Ding; Jun You (Food Hydrocolloids, 2025)

A novel role of PvUCP4 in Penaeus vannamei in response to Vibrio alginolyticus challenge - Zhengxinyu Liu; Caoyuan Han; FuHui Geng; XiaoTong Huang; BeiBei Dong; Yu Zhang; Weiguo Qian; Qingjian Liang (Fish & Shellfish Immunology, 2025)

Fusobacterium nucleatum-derived 3-indolepropionic acid promotes colorectal cancer progression via aryl hydrocarbon receptor activation in macrophages - Qi Song; Zhiliang Jin; Han Zhang; Kunqiao Hong; Beibei Zhu; Haisen Yin; Baoping Yu (Chemico-Biological Interactions, 2025)

Effects of polylactic acid microplastics on dissolved organic matter across soil types: Insights into molecular composition - Liying Chen; Hongkai Huang; Lanfang Han; Liang Chao; Xuanwei Zhang; Beibei Liu; Chenyan Luo; Weiling Mo; Yanpeng Cai; Zhifeng Yang (Journal of Hazardous Materials, 2025)

A methodology for evaluating the safety resilience of the existing tunnels induced by foundation pit excavation - Kaihang Han; Zhiyuan Zhai; Xiangsheng Chen; Chengping Zhang; Jiann-Wen Woody Ju; Xiaohua Bao; Shuying Wang; Beibei Hou (Tunnelling and Underground Space Technology, 2025)

Development of electrocoagulation/peracetic acid system to degrade chloramphenicol: Mechanisms and removal efficiency - Bingqian Zheng; Huanhuan Shi; Beibei Wang; Kehao Zhang; Yuran Han; Hongyou Wan; Wei Zhang; Hailong Wang; Liang Mao; Shixiang Gao; Qingguo Huang (Chemical Engineering Journal, 2025)

3D printed lanthanide-doped Ti4O7 reactive membrane for efficient electrochemical disinfection and degradation of antibiotic resistance genes - Kehao Zhang; Yuran Han; Peiheng Wang; Zhaoshuang Bu; Beibei Wang; Huanhuan Shi; Hailong Wang; Wei Zhang; Shixiang Gao; Qingguo Huang (Chemical Engineering Journal, 2024)

Vitamin C ameliorates D-galactose-induced senescence in HEI-OC1 cells by inhibiting the ROS/NF-κB pathway - Beibei Xu; Guanghui Wang; Luan Xu; Liya Ding; Shumin Li; Yuefeng Han (Molecular Biology Reports, 2024)

3D reconfigurable hydroxylated carbon nanotubes-based water evaporators with long-distance transportation for continuous vapor generation - Youqiang Huang; Pengjie Zhong; Ningning Zhu; Yinyan Li; Zhen Xiao; Keyu Han; Beibei Xu; Shiqing Xu; Gongxun Bai (Chemical Engineering Journal, 2024)

Electrochemical flow-through disinfection of Escherichia coli versus Staphylococcus aureus: Identifying impacts of flow patterns on efficiency - Peiheng Wang; Huanhuan Shi; Kehao Zhang; Yuran Han; Wei Zhang; Beibei Wang; Hailong Wang; Shiliang Liu; Qingguo Huang; Shixiang Gao (Chemical Engineering Journal, 2024)

Quantifying the negative effects of dissolved organic carbon of maize straw-derived biochar on its carbon sequestration potential in a paddy soil - Lanfang Han; Beibei Liu; Yu Luo; Liying Chen; Chuanxin Ma; Chao Xu; Ke Sun; Baoshan Xing (Soil Biology and Biochemistry, 2024)

Tailoring of orderly CeO2/Pt loaded Ti4O7 reactive electrochemical membranes for efficient electrooxidation of antimicrobial dichlorophen - Kehao Zhang; Yuran Han; Beibei Wang; Huanhuan Shi; Hailong Wang; Shixiang Gao; Qingguo Huang (Chemical Engineering Journal, 2024)

Effects of combined treatment with hydrogen-rich electrolyzed water and tea polyphenols on oxidative stress, intestinal injury and intestinal flora disruption in heat-stressed mice - Yao Zang; Beibei Zhang; Guosheng Zhang; Jie Hu; Dengqun Shu; Jiahong Han; Mengzhen Hu; Mingming Tu; Wenduo Qiao; Renxin Liu; Yitian Zang (Journal of Thermal Biology, 2024)

Experimental study on structural performance of 7A04-T6 high-strength aluminium alloy shear connections in and after fire - Zhongxing Wang; Chunyin Ma; Xiang Yun; Qinghua Han; Beibei Li; Zongyi Wang (Engineering Structures, 2024)

Spatial and temporal patterns of above- and below- ground biomass over the Tibet Plateau grasslands and their sensitivity to climate change - Yatang Wu; Fu Li; Jing Zhang; YiLiang Liu; Han Li; Bingrong Zhou; Beibei Shen; Lulu Hou; Dawei Xu; Lei Ding; Shiyang Chen; Xiaoni Liu; et al. (Science of The Total Environment, 2024)

Effects of transition-metal ions on the reduction of N-nitrosodimethylamine in water by zinc - Ying Han; Xiaoping Zheng; Beibei Jiang; Yuling Tang; Hongyuan Liu; Kemin Zhang; Yaping Guo; Jun Li (Journal of Environmental Chemical Engineering, 2024)

Responses of microeukaryotic community structure to a Phaeocystis globosa bloom in a semi-enclosed subtropical bay - Beibei Han; Rongjun Shi; Shufei Zhang; Anji Lian; Zexing Kuang; Fengxia Wu; Lingfeng Huang; Honghui Huang (Marine Environmental Research, 2024)

Effect of seawater on the performance of flat-tube solid oxide cell for CO2/H2O co-electrolysis - Meng Xiong; Beibei Han; Yan Yao; Anqi Wu; Yunfang Gao; Wanbing Guan (Fuel, 2024)

Nitrogen source affects non-aeration microalgal-bacterial biofilm growth progression and metabolic function during greywater treatment - Jiake Li; Beibei Wu; Meng Xu; Xuan Han; Yinuo Xing; Yu Zhou; Mengyao Ran; Yun Zhou (Bioresource Technology, 2024)

Two distinct neuroanatomical subtypes of migraine without aura revealed by heterogeneity through discriminative analysis - Hao Liu; Ruiping Zheng; Yong Zhang; Beibei Zhang; Haiman Hou; Jingliang Cheng; Shaoqiang Han (Brain Imaging and Behavior, 2023)

Coastal sediment heavy metal(loid) pollution under multifaceted anthropogenic stress: Insights based on geochemical baselines and source-related risks - Zexing Kuang; Huijuan Wang; Beibei Han; Yiyong Rao; Haixing Gong; Wanru Zhang; Yangguang Gu; Zhengqiu Fan; Shoubing Wang; Honghui Huang (Chemosphere, 2023)

The coupling and coordination degree of urban resilience system: A case study of the Chengdu–Chongqing urban agglomeration - Shan Han; Bo Wang; Yibin Ao; Homa Bahmani; Beibei Chai (Environmental Impact Assessment Review, 2023)

Loss of GLTSCR1 causes congenital heart defects by regulating NPPA transcription - Fengyan Han; Beibei Yang; Yan Chen; Lu Liu; Xiaoqing Cheng; Jiaqi Huang; Ke Zhou; Dandan Zhang; Enping Xu; Maode Lai; Bingjian Lv; Hongqiang Cheng; et al. (Angiogenesis, 2023)
Precise and specific spatiotemporal domains of gene expression regulation are critical for embryonic development. Recent studies have identified GLTSCR1 as a gene transcriptional elongation regulator in cancer research. However, the function of GLTSCR1, especially in embryonic development, remains poorly understood. Here, we found that GLTSCR1 was essential for cardiac development because Gltscr1 knockout (Gltscr1 −/− ) led to embryonic lethality in mice with severe congenital heart defects (CHDs). Ventricular septal defect and double outflow right ventricular were also observed in neural crest cells with conditional deletion of Gltscr1, which were associated with neonatal lethality in mice. Mechanistically, GLTSCR1 deletion promoted NPPA expression by coordinating the CHD risk G allele of rs56153133 in the NPPA enhancer and releasing the transcription factor ZNF740-binding site on the NPPA promoter. These findings demonstrated that GLTSCR1 acts as a candidate CHD-related gene.

scRNA-seq analysis reveals toxicity mechanisms in shrimp hemocytes subjected to nitrite stress - QingJian Liang; BeiBei Dong; Ang Li; LiTing Wu; Yu Zhang; Tao Han; Xing Liu (Chemosphere, 2023)

Bifunctional carbon nanofibrous interlayer embedded with cobalt single atoms for polysulfides trapping and catalysis in lithium-sulfur batteries - Beibei Song; Haoyue Zhao; Gang Zhao; Han Li; Can Ge; Guilong Yan; Jian Fang (Chemical Engineering Journal, 2023)

Genome-wide signatures of the geographic expansion and breeding of soybean - Ying-Hui Li; Chao Qin; Li Wang; Chengzhi Jiao; Huilong Hong; Yu Tian; Yanfei Li; Guangnan Xing; Jun Wang; Yongzhe Gu; Xingpeng Gao; Delin Li; et al. (Science China Life Sciences, 2023)

Multidimensional analysis of the essential elements in pregnant women's whole blood and characterization of maternal status by elemental pattern - Min Zhan; Wenbin Chen; Zhichao Wang; Xuhui She; Qiaoxuan Zhang; Heng Dong; Jun Yan; Zhuoyang Li; Liqiao Han; Haibiao Lin; Xianzhang Huang; Beibei Zhao (Journal of Trace Elements in Medicine and Biology, 2023)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

GITRL impairs the immunosuppressive function of MDSCs via PTEN-mediated signaling pathway in experimental Sjögren syndrome - Jie Tian; Beibei Zhang; Qingfang Yuan; Xueqing Sun; Na Peng; Bo Zhu; Chang Liu; Xiaoran Wang; Man Han; Meng Cao; Fan Xiao; Shengjun Wang; et al. (Inflammation Research, 2022)

Deubiquitylatinase inhibitor b-AP15 induces c-Myc-Noxa-mediated apoptosis in esophageal squamous cell carcinoma - Beibei Sha; Xiaoyu Chen; Han Wu; Miaomiao Li; Jianxiang Shi; Longhao Wang; Xingge Liu; Ping Chen; Tao Hu; Pei Li (Apoptosis, 2019)

Overexpression of AtAGT1 promoted root growth and development during seedling establishment - Rui Wang; Lin Yang; Xiaofang Han; Yuhong Zhao; Ling Zhao; Beibei Xiang; Yerong Zhu; Yanling Bai; Yong Wang (Plant Cell Reports, 2019)

Late Quaternary glaciations in the Cogarbu valley, Bhutanese Himalaya - Xu Peng; Yixin Chen; Gengnian Liu; Beibei Liu; Yingkui Li; Qing Liu; Yesong Han; Weilin Yang; Zhijiu Cui (Journal of Quaternary Science, 2019)
This study investigates the late Quaternary glacial history of the Cogarbu valley on the northern slopes of the Bhutanese Himalaya using 10 Be surface exposure dating. Five major glacial events were constrained based on 28 10 Be exposure ages. The equilibrium line altitude (ELA) of the oldest and most extensive glacial event (M5–M9) is ∼489 m lower than the present, followed by four other events (M4, M3, M2 and M1) with ELA depressions of ∼452, ∼200, ∼76 and ∼42 m, respectively. The exposure ages of the oldest glacial event (M5–M9) are ∼23.4–19.1 ka, corresponding to the global Last Glacial Maximum (gLGM). The second (M4, ∼15.8 ka) and the third oldest events (M3, ∼11.5 ka) coincide with the Heinrich‐1 and Younger Dryas event, respectively. The fourth oldest glacial event (∼1.2–0.82 ka) occurred during the Late Holocene. The latest glacial event (∼0.77–0.53 ka) represents the Little Ice Age glacial advances. These glacial events are broadly synchronous with those from other regions across the monsoon‐influenced Himalaya. All these events occurred during the cold periods, despite relatively dry conditions. It appears that temperature is the major factor driving glacial fluctuations since the gLGM in the Bhutanese Himalaya.

Dynamic-Change Laws of the Porosity and Permeability of Low- to Medium-Rank Coals under Heating and Pressurization Treatments in the Eastern Junggar Basin, China - Gang Wang; Yong Qin; Jian Shen; Shuyuan Chen; Beibei Han; Xiaoting Zhou (Journal of Earth Science, 2018)

Trace element stoichiometry of submerged macrophytes in Yangtze floodplain lakes and Yunnan plateau lakes (China) - Wei Xing; Haoping Wu; Beibei Hao; Han Liu; Guihua Liu (Aquatic Sciences, 2017)

Expression pattern of phb2 and its potential function in spermatogenesis of scallop (Chlamys farreri) - Tiantian Han; Xiaoshi Ma; Shaoshuai Liang; Beibei Gao; Zhifeng Zhang (Journal of Ocean University of China, 2015)